An Integrated Performance Index for Decentralized Water Supply Systems: A Case Study of SiPAS in the Brantas River Basin - Ussy Andawayanti; Runi Asmaranto; M. Amar Sajali; Ery Suhartanto; Mustafa Mukti Hidayat; Rizki Tri Utami (Postgraduate, University of Mataram, 2025)
To develop and validate an Integrated Performance Index Model (IPIM) for evaluating Simple Water Supply Systems (SiPAS) in the Brantas River Basin, Indonesia. We surveyed, audited, and interviewed stakeholders at 31 SiPAS sites. Latent constructs were tested using SEM–PLS, and dimension weights were optimized with the Generalized Reduced Gradient method. The model explained system performance well (R² = 0.95) and showed high predictive reliability. The technical dimension exerted the strongest influence (72.10%), followed by managerial (26.70%) and social (15.10%) factors. The index differentiated low and high performing sites and was consistent with field audit findings. A companion mobile application enabled real time reporting and feedback to strengthen community participation. IPIM provides a concise, scalable framework for assessing decentralized water supply, prioritizing technical improvements while supporting managerial and social strengthening, and can inform investment and governance decisions for rural water services.